Preparation method and application of UiO-66-NH2-lac-SA membrane
UiO-66-NH2 carrier was synthesized by hydrothermal method and covalently fixed with laccase to prepare UiO-66-NH2@Lac@SA membrane, which solved the technical problems of dye treatment in industrial wastewater and achieved efficient dye degradation effect , especially the degradation rate of malachite green dye reached 82.15%.
Patent Information
- Application Number
- CN202410863643.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-29
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively treat pollutants, especially dyes, in industrial wastewater, and biocatalytic technology has problems of insufficient stability and dispersion in this regard.
UiO-66-NH2 carrier was synthesized by hydrothermal method, and covalently fixed with laccase using enzyme immobilization technology. Catalyst particles were embedded by in situ encapsulation method to prepare UiO-66-NH2@Lac@SA membrane for use in-situ Wastewater treatment.
UiO-66-NH2@Lac@SA membrane exhibits good acid resistance, dispersion and structural stability, especially the degradation effect of malachite green dye, reaching more than 82.15%, and the enzyme activity is at the laccase concentration of 7 mg/mL. and the maximum is reached at 1h.
Smart Images

Figure CN119161029A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite membranes, and specifically to a preparation method and application of a UiO-66-NH2@Lac@SA membrane. Background Art
[0002] Currently, many pharmaceutical factories and printing and dyeing factories produce a large amount of wastewater during the production process, and the pollutants in it remain in the environment, which will greatly endanger human survival. Therefore, it is necessary and urgent to adopt effective treatment methods to treat polluted wastewater. Obviously, biocatalysis technology can solve the problem of wastewater pollution more easily by utilizing the characteristics of high enzyme catalysis efficiency and mild environment. Summary of the invention
[0003] The technical problem to be solved by the present invention is that in view of the deficiencies of the above-mentioned prior art, a method for preparing a UiO-66-NH2@Lac@SA membrane is provided. The method synthesizes a UiO-66-NH2 carrier with strong acid resistance, good dispersibility and structural stability by a hydrothermal method, covalently fixes the carrier with laccase by enzyme immobilization technology, and continues to achieve the internal encapsulation of the catalyst particle membrane by an in-situ encapsulation method to obtain a UiO-66-NH2@Lac@SA membrane. The UiO-66-NH2@Lac@SA membrane can be used for wastewater treatment and dye degradation.
[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a UiO-66-NH2@Lac@SA membrane, characterized in that the method comprises:
[0005] S1. Preparation of UiO-66-NH2 carrier
[0006] 0.976 g zirconium chloride and 0.752 g 2-aminoterephthalic acid were dissolved in 240 mL N, N-dimethylacetamide at the same time, and then 7.2 mL glacial acetic acid was added under stirring, and then stirring was continued for 1 hour. After being fully mixed, ultrasonication was performed for 10 minutes, and then transferred to a high-temperature autoclave with a polytetrafluoroethylene liner, heated at 120°C for 24 hours, cooled to room temperature and centrifuged, and then washed with DMF and anhydrous methanol for multiple times. After precipitation, it was placed at 60°C and dried for 12 hours to obtain a pink powder UiO-66-NH2 carrier;
[0007] S2, UiO-66-NH2 carrier modification
[0008] The UiO-66-NH2 carrier was added to a 10 mM α-lipoic acid solution, and then stirred for 1 hour, and then centrifuged at 10000 rpm for 4 minutes, the supernatant was discarded, and the mixture was washed three times by centrifugation with deionized water. After discarding the supernatant, the precipitate was retained to obtain a modified UiO-66-NH2 carrier precipitate;
[0009] S3. Preparation of immobilized enzyme solution
[0010] 1 mL of a 1:1 mixed solution of 0.75 mM 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.15 mM N-hydroxysuccinimide was added to the modified UiO-66-NH2 carrier precipitate, and the mixture was stirred for 1 h, and then centrifuged and washed three times to obtain a carrier precipitate. Then, 3 mL of 0.01 M phosphate buffer and 1 mL of laccase solution were added to the carrier precipitate. After stirring and solidifying for 1.5 h, the precipitate was centrifuged and washed three times to obtain a covalent catalyst UiO-66-NH2@Lac. Then, 1 mL of ultrapure water was added to the covalent catalyst to obtain an immobilized laccase solution.
[0011] S4, UiO-66-NH2@Lac@SA membrane preparation
[0012] The defoamed sodium alginate membrane stock solution was mixed with the immobilized laccase solution in a volume ratio of 5 mL:50 μL, added to the mold and dried at low temperature to form a film, and then a 2% mass concentration of calcium chloride solution was added to cross-link for 2 minutes to facilitate peeling off the membrane. The membrane was rinsed with ultrapure water and dried again to obtain the UiO-66-NH2@Lac@SA membrane.
[0013] Preferably, the usage ratio of zirconium chloride, 2-aminoterephthalic acid, N,N-dimethyldiamide solution and glacial acetic acid in S1 is 0.976 g: 0.752 g: 240 mL: 7.2 mL.
[0014] Preferably, the centrifugal speed in S1, S2 and S3 is 10000 rpm and the time is 4-5 min.
[0015] Preferably, the usage ratio of UiO-66-NH2 carrier and α-lipoic acid solution in S2 is 0.06 g:1 mL.
[0016] Preferably, the pH of the phosphate buffer in S3 is 7.2-7.4; and the concentration of the laccase solution is 5-9 mg / mL.
[0017] Preferably, the preparation method of the sodium alginate membrane stock solution in S4 is: add 1-5.5g sodium alginate to 100mL ultrapure water to obtain 0.01-0.055g / mL sodium alginate solution, and then add 0.4g glycerol and stir evenly to obtain the sodium alginate membrane stock solution.
[0018] The present invention also discloses an application of UiO-66-NH2@Lac@SA membrane.
[0019] The UiO-66-NH2@Lac@SA membrane is used for wastewater treatment.
[0020] Preferably, the UiO-66-NH2@Lac@SA membrane is used to degrade dyes.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] 1. The present invention can synthesize a UiO-66-NH2 carrier with good acid resistance, good dispersibility and stable structure by a hydrothermal method, and then fix the laccase on the UiO-66-NH2 carrier by a covalent coupling method. It is found that when the laccase concentration is 7 mg / mL and the immobilization time is 1 h, the relative enzyme activity is the highest. Based on this, the UiO-66-NH2@Lac particles are embedded in the sodium alginate membrane to obtain the UiO-66-NH2@Lac@SA membrane. The UiO-66-NH2@Lac@SA membrane has a strong degradation effect on dyes, especially the best degradation effect on malachite green, which can reach 82.15%.
[0023] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 SEM images of UiO-66-NH2, UiO-66-NH2@Lac, and UiO-66-NH2@Lac@SA films prepared in Example 1 of the present invention; (a): UiO-66-NH2 crystals at a magnification of 200nm, (b): UiO-66-NH2 crystals at a magnification of 500nm, (c): UiO-66-NH2@Lac crystals at a magnification of 200nm, (d): UiO-66-NH2@Lac crystals at a magnification of 500nm, (e): UiO-66-NH2@Lac@SA film at a magnification of 5μm, (f): SEM image of UiO-66-NH2@Lac at a magnification of 500nm.
[0025] Figure 2 The curve is the effect of the addition amount of laccase on the effect of immobilized enzyme.
[0026] Figure 3 This is the relative enzyme activity curve of the immobilized enzyme obtained by UiO-66-NH2@Lac at different stirring and fixing times in the present invention.
[0027] Figure 4 This is a bar graph showing the degradation rates of the UiO-66-NH2@Lac@SA membranes with different SA contents for dye solutions of the same concentration.
[0028] Figure 5This is a bar graph of the degradation rate of the UiO-66-NH2@Lac@SA membranes with different UiO-66-NH2@Lac contents of the present invention for dye solutions of the same concentration.
[0029] Figure 6 This is the thermal stability diagram of free laccase, UiO-66-NH2@Lac and UiO-66-NH2@Lac@SA membrane of the present invention.
[0030] Figure 7 Graph showing the acid-base stability of free laccase, UiO-66-NH2@Lac and UiO-66-NH2@Lac@SA membranes of the present invention.
[0031] Figure 8 The stability of free laccase, UiO-66-NH2@Lac and UiO-66-NH2@Lac@SA membrane denaturants of the present invention
[0032] Fig. 9 It is the relative enzyme activity of free laccase, UiO-66-NH2@Lac and UiO-66-NH2@Lac@SA membrane under the action of different metal ions.
[0033] Fig.10 This is the dye degradation effect of the UiO-66-NH2@Lac@SA membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] Example 1
[0035] A method for preparing a UiO-66-NH2@Lac@SA film in this embodiment comprises:
[0036] S1. Preparation of UiO-66-NH2 carrier
[0037] 0.976g zirconium chloride and 0.752g 2-aminoterephthalic acid were dissolved in 240mL N, N-dimethylacetamide (DMF) at the same time, and then 7.2mL glacial acetic acid was added to the above solution under stirring, and stirred at 550rpm on a magnetic stirrer for 1h. After the drugs were fully mixed, ultrasonic was applied for 10min, and then transferred to a high-temperature autoclave with a polytetrafluoroethylene liner and reacted at 120℃ for 24h. After the reactor and the internal solution were cooled to room temperature, the internal suspension was centrifuged at 10000rpm for 5min, washed with DMF and anhydrous methanol for 3 times respectively, and the precipitate was dried at 60℃ for 12h to obtain a pink powder UiO-66-NH2 carrier;
[0038] S2, UiO-66-NH2 carrier modification
[0039] Weigh 0.06 g of UiO-66-NH2 carrier and place it in a small beaker, add 1 mL of 10 mM α-lipoic acid solution, stir at 550 rpm for 1 h on a magnetic stirrer, centrifuge at 10000 rpm for 4 min, discard the supernatant, wash three times with deionized water by centrifugation, discard the supernatant and retain the precipitate to obtain the modified UiO-66-NH2 carrier precipitate;
[0040] S3. Preparation of immobilized enzyme solution
[0041] 1 mL of the 1:1 mixed solution was added to the modified UiO-66-NH2 carrier precipitate, and the mixture was stirred for 1 h. The mixture was transferred to a centrifuge tube and centrifuged and washed three times. Then, 3 mL of 0.01 M phosphate buffer solution with a pH of 7.2 to 7.4 and 1 mL of 7 mg / mL laccase solution were added to the carrier precipitate. The mixture was stirred for 1.5 h and centrifuged and washed three times to obtain the covalent catalyst UiO-66-NH2@Lac. Then, 1 mL of ultrapure water was added to the covalent catalyst UiO-66-NH2@Lac to obtain the immobilized laccase solution.
[0042] The mixed solution is prepared by mixing a 0.75 mM 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) solution and a 0.15 mM N-hydroxysuccinimide (NHS) solution in a volume ratio of 1:1.
[0043] S4, UiO-66-NH2@Lac@SA membrane preparation
[0044] Take multiple 100mL ultrapure water in a conical flask, slowly add 4.5g of sodium alginate into it respectively, and after it is completely dissolved, add 0.4g of glycerol and stir evenly to make a sodium alginate membrane stock solution. After standing to defoam, the defoamed sodium alginate membrane stock solution and the immobilized laccase solution are mixed in a volume ratio of 5mL:50μL, added to the mold and dried at low temperature to form a film, and then a calcium chloride solution with a mass concentration of 2% is added for cross-linking for 2min, so that the membrane can be easily peeled off, and rinsed with ultrapure water. After drying again, it is a UiO-66-NH2@Lac@SA membrane.
[0045] Figure 1SEM images of UiO-66-NH2, UiO-66-NH2@Lac, and UiO-66-NH2@Lac@SA membranes prepared in Example 1 of the present invention; (a): UiO-66-NH2 crystals at a magnification of 200nm, (b): UiO-66-NH2 crystals at a magnification of 500nm, (c): UiO-66-NH2@Lac crystals at a magnification of 200nm, (d): UiO-66-NH2@Lac crystals at a magnification of 500nm, (e): UiO-66-NH2@Lac@SA membrane at a magnification of 5μm, (f): SEM image of UiO-66-NH2@Lac at a magnification of 500nm. Figure 1 (a) and (b) show that both UiO-66-NH2 and UiO-66-NH2@Lac present regular polyhedrons. Among them, the particle size of UiO-66-NH2 is less than 100nm. In addition, compared with UiO-66-NH2, UiO-66-NH2@Lac is slightly larger, but both have regular polyhedral morphology, and the particles are small and dispersed more evenly. The support layer of the sodium alginate membrane has a reticular pore structure, which provides a greater possibility for the retention of catalyst particles. Figure 1 In the enzyme membrane shown in (e), at a magnification of 5 μm, it can be observed that UiO-66-NH2@Lac is uniformly embedded in the sodium alginate membrane. Although the surface of the UiO-66-NH2@Lac@SA membrane is relatively rough, the increased specific surface area due to the wrinkles on the surface is conducive to the anchoring of the immobilized enzyme. The UiO-66-NH2@Lac@SA membrane has many holes, which are conducive to promoting the increase of pure water flux and also facilitate the reaction of UiO-66-NH2@Lac with the substrate. In addition, UiO-66-NH2@Lac is soluble in sodium alginate but does not destroy the membrane structure, and no large particles appear on the membrane surface, which indicates that UiO-66-NH2@Lac has good discreteness.
[0046] Example 2
[0047] In this example, the effect of the concentration of the laccase solution described in S3 on the activity of the prepared UiO-66-NH2@Lac was investigated, so as to screen out the optimal concentration of the laccase solution. Therefore, in this example, UiO-66-NH2@Lac prepared under the conditions of laccase concentration of 1 mg / mL, 3 mg / mL, 5 mg / mL, and 9 mg / mL was prepared, and the other conditions were the same as those in Example 1.
[0048] Determination of enzyme activity: The reaction mixture consists of 0.3 mM 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), ABTS, 100 mM sodium acetate buffer (pH 4.5) and appropriate amounts of free and immobilized laccase solutions. 0.4 mL of 0.3 mM ABTS was added to 3 mL of sodium acetate buffer, the initial value was recorded, and then 50 μL of laccase solution was added to start the reaction.
[0049] For immobilized laccase: first react the immobilized enzyme with the substrate for 4 minutes, then centrifuge at 11000rpm for 15s, and measure the OD2 value of the supernatant; △OD is composed of the difference before and after the reaction. Before the reaction, the empty carrier is added to the reaction system and centrifuged for 15s, which is OD1, △OD=OD2-OD1
[0050] For free enzyme, the absorbance value change before and after the reaction was recorded after 4 minutes of reaction.
[0051] Calculation formula:
[0052]
[0053] Where: ΔA – change in absorbance within reaction time t;
[0054] t——response time, in min;
[0055] V1——total volume of solution, in mL;
[0056] V2——the volume of enzyme solution added, in mL;
[0057] ε ABTS+ The molar extinction coefficient is 3.6×10 4 L·mol -1 cm -1
[0058] Effects of five laccase concentrations on the activity of prepared UiO-66-NH2@Lac, plotted according to experimental results Figure 2 ,from Figure 2It can be seen that when the laccase concentration is 7 mg / mL, UiO-66-NH2@Lac has the highest activity. Although the strong interaction cannot avoid the destruction of the active site of laccase, the enzyme activity after immobilization cannot directly contact the substrate, reducing the mass transfer resistance, and the enzyme activity will still increase with the increase of enzyme concentration. However, the immobilization of laccase at too high a concentration will significantly reduce the recovery of enzyme activity. The aggregation of high-concentration laccase molecules will cover some active sites, increase steric hindrance, and prevent further binding of substrate and laccase. When the initial enzyme concentration is 7 mg / mL, the enzyme activity is the highest, and the initial concentration is 5 mg / mL. The corresponding enzyme activity recovery rate also remains at a high level. When the enzyme concentration continues to increase, the enzyme activity recovery rate will decrease. Therefore, the optimal initial enzyme concentration of the immobilized enzyme is determined to be 7 mg / mL after comprehensive consideration.
[0059] Example 3
[0060] This application studies the effect of different laccase stirring and curing times in step S3 on the activity of the prepared UiO-66-NH2@Lac, so as to screen out the optimal stirring and curing time. In this example, the stirring and curing time can also be 0.5, 1, 2, and 2.5 h, and the other conditions are the same as the method in Example 1.
[0061] Figure 3 The relative enzyme activity curve of the immobilized enzyme obtained by UiO-66-NH2@Lac with different stirring and fixing time will have a certain impact on the implementation of the enzymatic reaction. When the concentration of the laccase solution is determined to be 7 mg / mL, the different immobilization times and their corresponding immobilized enzyme activities are as follows Figure 3 When the immobilization time is 1h, the immobilized enzyme activity is the highest, which indicates that the enzyme molecules have been successfully immobilized on the UiO-66-NH2 carrier, thus affecting the reaction rate of the enzyme. The enzyme activity gradually decreases with the extension of time. This is because the longer the immobilization time, the greater the physical damage to the catalyst particles. Therefore, the optimal time for immobilizing laccase is determined to be 1h.
[0062] Example 4
[0063] This example studies the effect of the addition amount of sodium alginate (SA) of 1, 1.5, 2, 2.5, 3, 3.5, 4, 5, and 5.5 g in the sodium alginate membrane stock solution in step S4 on the degradation efficiency of the UiO-66-NH2@Lac@SA membrane. The other conditions are the same as those in Example 1.
[0064] Place the prepared enzyme membrane into dye solutions of different concentrations, measure the sample concentration before and after enzyme treatment, and calculate the degradation efficiency. The operation is as follows:
[0065] (1) Malachite green standard curve
[0066] Weigh 0.1 g of malachite green (MG) powder and dissolve it in 100 mL of ultrapure water to prepare a 1 g / L malachite green mother solution, and take 0, 0.25, 0.5, 0.75, 1, 1.25, 1.5, 1.75, 2, and 2.5 mL of malachite green mother solution in 50 mL colorimetric tubes respectively; add ultrapure water to dilute to the 50 mL mark to prepare standard solutions; preheat the ultraviolet spectrophotometer; set the measuring wavelength to 617 nm, fill 3-4 mL of ultrapure water into the cuvette to adjust to 0, measure and record the absorbance OD values of malachite green of different concentrations; use the obtained data with the malachite green concentration as the x-axis and the absorbance value as the y-axis to draw a standard curve and obtain the regression equation.
[0067] (2) Degradation of malachite green by UiO-66-NH2@Lac / LMR
[0068] Pipette 3-4mL of 16mg / L malachite green solution into a cuvette and record the OD value. Then add LMR and a certain amount of immobilized enzyme solution into a 50mL Erlenmeyer flask containing 20mL of 16mg / L malachite green solution, shake and adsorb on a shaker at 150rpm in the dark for 2.5h, pipette 3-4mL of supernatant and record the OD value after adsorption. Calculate the adsorption rate by the OD value, and the degradation rate is equal to 100% minus the adsorption rate.
[0069] Sodium alginate is a linear polymer compound. Some of the molecular chains in the middle cross-link with other substances to form a gel. When the molecular chains in SA come into contact with calcium ions, a chemical reaction will occur to form a solid gel. However, the pure sodium alginate film is brittle and the film-forming effect is poor. In order to increase its performance, glycerol solution is added to the sodium alginate film as a plasticizer. In the early stage of the experiment, it was thought that the flexibility of the sodium alginate film could be increased, but it was found in the experiment that the addition of glycerol did not achieve the expected purpose. On the contrary, dissolution occurred during the degradation of malachite green by the enzyme film. In addition, the study also found that when the concentration of sodium alginate is low, its viscosity is relatively small and the film is formed quickly, but the film is thin. When the sodium alginate content is lower than a certain level, the pores of the prepared enzyme membrane are larger, and the particles of UiO-66-NH2@Lac will leak the catalyst particles in the enzyme due to their small size. When the concentration of sodium alginate is high, the interaction between the molecular chains is large and the cross-linking is very tight. The solution has high viscosity, slow film formation, thick and fragile. If UiO-66-NH2@Lac is fixed continuously, the pore size on the membrane surface will be dense and small, so that UiO-66-NH2@Lac cannot fully contact with the substrate, thereby reducing the apparent reaction rate of the enzyme membrane. Therefore, when the amount of sodium alginate is 4.5g, the degradation efficiency reaches a maximum of 77.52%.
[0070] Example 5
[0071] This example studies the mixing of 5 mL of sodium alginate membrane stock solution in step S4 with 10, 20, 30, 40, 50, 60, 70, 80, 90, and 100 μL of laccase solution, respectively, to prepare UiO-66-NH2@Lac@SA membranes with different UiO-66-NH2@Lac contents, and explores the effect of UiO-66-NH2@Lac content on the degradation efficiency of the membrane. Other conditions are the same as those in Example 1. The membrane degradation efficiency test was carried out on UiO-66-NH2@Lac@SA membranes with different UiO-66-NH2@Lac contents. The test method is as follows: the prepared enzyme membrane is placed in dye (malachite green) solutions of different concentrations, the sample concentrations before and after enzymatic treatment are measured, and the degradation efficiency is calculated. The results are as follows: Figure 5 shown.
[0072] Different amounts of UiO-66-NH2@Lac were added to a certain amount of sodium alginate film-forming liquid, and the optimal addition amount was determined by the degradation effect on malachite green. As the amount of UiO-66-NH2@Lac added gradually increased, the effect of the enzyme membrane on the degradation of malachite green increased due to the increase in the content of immobilized enzyme. However, in fact, when the amount exceeded a certain amount, the immobilized enzyme would cause the active centers of the laccase to cover each other due to the increased content of enzyme particles, which would reduce the catalytic rate. Figure 5 When the content was greater than 40 μL, the degradation rate gradually decreased, and when the added amount was 40 μL, the degradation rate reached 85.70%.
[0073] Performance test
[0074] (1) Thermal stability
[0075] The thermal stability of free laccase, immobilized laccase and enzyme membrane was studied. Figure 6 . Temperature will have a certain effect on the activity of free laccase. When the temperature is 50°C, the relative enzyme activity is the highest. After that, when the temperature continues to rise to 80°C, the enzyme activity is completely lost. There are two reasons for this: first, the increase in temperature makes the active groups such as hydroxyl and carboxyl in the laccase molecular structure become active, and the enzyme activity gradually increases; second, when the temperature rises further, the spatial structure of the enzyme changes, which eventually makes the enzyme easily inactivated.
[41] In comparison, in the immobilized system, the optimum temperature of UiO-66-NH2@Lac and UiO-66-NH2@Lac@SA is 70°C. This is because the spatial structure of laccase is protected by the UiO-66-NH2 carrier and the membrane substrate, which prevents the change of the natural conformation of laccase. This greatly reduces the effect of temperature on enzyme activity, making its high temperature resistance better than that of free laccase.
[0076] (2) Acid-base stability study
[0077] The spatial conformation of laccase is easily affected by the acidity and alkalinity of the environment. Too high or too low pH in the environment will reduce the activity of laccase or even inactivate it. Samples were treated with sodium acetate buffer of different pH values, such as Figure 7 As shown, when the pH is 6, the free laccase activity is the strongest, and when it is alkaline, the free laccase activity tends to zero. When the pH is between 6-7, both UiO-66-NH2@Lac and UiO-66-NH2@Lac@SA show high enzyme activity and high acid-base tolerance. In addition, the enzyme activity is measured and it is known that the enzyme activity of UiO-66-NH2@Lac is higher than that of UiO-66-NH2@Lac@SA membrane. This is because the intervention of the outermost membrane will directly affect the mass transfer process of the entire enzymatic reaction, which will directly affect the entire process of the enzymatic reaction. In addition, by Figure 7 It can also be concluded that the enzyme conformation of UiO-66-NH2@Lac is relatively stable at pH 3-7, and can maintain more than 60% of the initial enzyme activity, while the UiO-66-NH2@Lac@SA membrane adapts to a wider pH range. When the pH is 11, it still maintains 30.77% of the original activity compared with the control. This further illustrates that the immobilized carrier can maintain laccase in a relatively stable environment, reduce the damage to the spatial conformation of laccase when the external environment changes in acidity and base, and further improve the acid-base stability of laccase.
[0078] (3) Denaturant stability
[0079] Treating samples with different denaturants under the same conditions will damage the activity of laccase and immobilized enzyme to a certain extent, reducing the activity of laccase. Figure 8 ,from Figure 8 As can be seen from the above, phenol has the greatest impact on free laccase, and the activity after treatment is only 6.33% of the initial enzyme activity. The second is ethanol, which is a strong denaturant and can be miscible with water in any proportion, which will directly take away the structural water in the free enzyme. In comparison, urea is the weakest denaturant among these denaturants. , The activity after treatment is only 51.9% of the initial enzyme activity. In comparison, the tolerance of the immobilized system to denaturants is significantly enhanced. The influence trend of denaturants on UiO-66-NH2@Lac is similar to that of free enzymes, while the resistance of the enzyme membrane to ethanol is much higher than that of other denaturants. This may be because the enzyme membrane reduces the influence of ethanol on the laccase molecules by preventing the loss of "essential water", so the enzyme membrane will show a strong tolerance to organic solvents.
[0080] (4) Metal ion stability
[0081] 3 mL of 0.5 mmol / L Cu(NO3)2, FeCl3, MnSO4, CoCl2, and AgCl solution were added to a centrifuge tube, and 1 mL of free enzyme was added to the centrifuge tube for 30 min. After centrifugation at 4000 rpm for 3 min, the tube was washed three times with deionized water, the supernatant was discarded, and 1 mL of deionized water was added to dissolve the precipitate to the original volume, and the enzyme activity was immediately measured.
[0082] 3 mL of 0.5 mmol / L Cu(NO3)2, FeCl3, MnSO4, CoCl2, and AgCl solution were added to a centrifuge tube respectively, and 1 mL of immobilized enzyme was added to the centrifuge tube for 30 min. After centrifugation at 4000 rpm for 3 min, the tube was washed three times with deionized water, the supernatant was discarded, and 1 mL of deionized water was added to dissolve the precipitate to the original volume, and the enzyme activity was immediately measured.
[0083] For UiO-66-NH2@Lac@SA membrane (LMR), the UiO-66-NH2@Lac@SA membrane was placed in 10 mL and 0.5 mmol / L Cu(NO3)2, FeCl3, MnSO4, CoCl2, and AgCl solutions, respectively, and treated for 30 min. Then the membrane was taken out and dried at low temperature to its original volume, and the enzyme activity was measured immediately after treatment.
[0084] Fig. 9 is the relative enzyme activity of free laccase, UiO-66-NH2@Lac and UiO-66-NH2@Lac@SA membrane under the action of different metal ions, among which Ag + The inhibitory effect of Fe is the strongest, which can completely inactivate free laccase. This is because metal ions occupy the binding site between the substrate and the enzyme, changing the spatial conformation of the enzyme, thus significantly inhibiting the enzyme activity. 3+ and Mn 2+ The inhibition of laccase can reach more than 80%, while Cu 2+ and Co 2+ The inhibitory effect is relatively weak. The five different metal ions have similar effects on the two immobilized enzymes, but the inactivation effect is much smaller than that of free laccase. This is because the intervention of the carrier will effectively prevent the damage of heavy metal ions to the enzyme and increase the firmness of the enzyme active conformation to prevent the enzyme molecule from stretching and deforming. In addition, Fe 3+ The inhibitory effect on UiO-66-NH2@Lac is weaker than that on UiO-66-NH2@Lac and LMR. Among these metal ions, Cu2+ has the least effect on laccase, which is consistent with the 2+ It may be related to the atoms in the active center of laccase. 2+ When the concentration is low, the effect on the enzyme is weak, and even when the concentration is appropriately selected, it may show a certain activation effect on laccase.
[0085] (5) Dye adsorption by UiO-66-NH2@Lac@SA membrane
[0086] The UiO-66-NH2@Lac@SA membrane prepared in Example 1 was used to perform degradation experiments on 7 dyes, including malachite green, crystal violet, chrome black T, acid fuchsin, methyl green, methyl orange, and methylene blue. The experimental process was as follows: 3-4 mL of different dye solutions were pre-absorbed into a cuvette and the OD value was recorded. Then the UiO-66-NH2@Lac@SA membrane and the immobilized enzyme solution were added to a conical flask containing 20 mL of different dye solutions of a certain concentration, and adsorbed on a shaker at 150 rpm in the dark for 2.5 h, 3-4 mL of the supernatant was aspirated, and the OD value after adsorption was recorded. The degradation rate was calculated by the OD value.
[0087] The results are as follows Fig.10 The UiO-66-NH2@Lac@SA membrane prepared in Example 1 has different degradation effects on the seven selected dyes, as shown in FIG. Fig.10 As shown in the figure, the degradation effect of UiO-66-NH2@Lac@SA membrane on methyl green in triphenylmethane dyes is the most obvious, and the total dye degradation rate reaches 97.43% within 2.5 hours. At the same time, the degradation effect on dyes belonging to the same category is above 80%, among which the degradation rate of crystal violet solution reaches 89.67%, followed by acid fuchsin solution and malachite green solution, with degradation rates reaching 87.22% and 85.70% respectively. The degradation effect of UiO-66-NH2@Lac@SA membrane on thiazolinone dyes (methylene blue) is also very significant, with a degradation rate of 93.89%. However, UiO-66-NH2@Lac@SA membrane has almost no degradation effect on some dyes, such as azo dyes (such as methyl orange and chrome black T). In the 2.5h degradation process, the degradation effect is less than 35%. The above data reflect that the enzyme membrane reactor has a certain degradation effect on most dyes.
[0088] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a UiO-66-NH2@Lac@SA membrane, characterized in that: The method includes: S1. Preparation of UiO-66-NH2 carrier 0.976 g zirconium chloride and 0.752 g 2-aminoterephthalic acid were dissolved in 240 mL N, N-dimethylacetamide at the same time, and then 7.2 mL glacial acetic acid was added under stirring, and then stirring was continued for 1 hour. After being fully mixed, ultrasonication was performed for 10 minutes, and then transferred to a high-temperature autoclave with a polytetrafluoroethylene liner, heated at 120°C for 24 hours, cooled to room temperature and centrifuged, and then washed with DMF and anhydrous methanol for multiple times. After precipitation, it was placed at 60°C and dried for 12 hours to obtain a pink powder UiO-66-NH2 carrier; S2, UiO-66-NH2 carrier modification The UiO-66-NH2 carrier was added to a 10 mM α-lipoic acid solution, and then stirred for 1 hour, and then centrifuged at 10000 rpm for 4 minutes, the supernatant was discarded, and the mixture was washed three times by centrifugation with deionized water. After the supernatant was discarded, the precipitate was retained to obtain a modified UiO-66-NH2 carrier precipitate; S3. Preparation of immobilized enzyme solution 1 mL of a 1:1 mixed solution of 0.75 mM 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide and 0.15 mM N-hydroxysuccinimide was added to the modified UiO-66-NH2 carrier precipitate, and the mixture was stirred for 1 h, and then centrifuged and washed three times to obtain a carrier precipitate. Then, 3 mL of 0.01 M phosphate buffer and 1 mL of laccase solution were added to the carrier precipitate. After stirring and solidifying for 1.5 h, the precipitate was centrifuged and washed three times to obtain a covalent catalyst UiO-66-NH2@Lac. Then, 1 mL of ultrapure water was added to the covalent catalyst to obtain an immobilized laccase solution. S4, UiO-66-NH2@Lac@SA membrane preparation The defoamed sodium alginate membrane stock solution was mixed with the immobilized laccase solution in a volume ratio of 5 mL:50 μL, added to the mold and dried at low temperature to form a film, and then a 2% mass concentration of calcium chloride solution was added to cross-link for 2 minutes to facilitate peeling off the membrane. The membrane was rinsed with ultrapure water and dried again to obtain the UiO-66-NH2@Lac@SA membrane.
2. A multi-mode vehicle classification prevention and control integrated system according to claim 1, characterized in that: The amount ratio of zirconium chloride, 2-aminoterephthalic acid, N,N-dimethyldiamide solution and glacial acetic acid in S1 is 0.976 g: 0.752 g: 240 mL: 7.2 mL.
3. The method for preparing a UiO-66-NH2@Lac@SA membrane according to claim 1, characterized in that: The centrifugation speed in S1, S2 and S3 is 10000 rpm and the time is 4-5 min.
4. The method for preparing a UiO-66-NH2@Lac@SA membrane according to claim 1, characterized in that: The dosage ratio of UiO-66-NH2 carrier and α-lipoic acid solution in S2 is 0.06 g:1 mL.
5. The method for preparing a UiO-66-NH2@Lac@SA membrane according to claim 1, characterized in that: The pH of the phosphate buffer in S3 is 7.2-7.4; the concentration of the laccase solution is 5-9 mg / mL.
6. The method for preparing a UiO-66-NH2@Lac@SA membrane according to claim 1, characterized in that: The preparation method of the sodium alginate membrane stock solution in S4 is: add 1-5.5g of sodium alginate into 100mL of ultrapure water to obtain a 0.01-0.055g / mL sodium alginate solution, then add 0.4g of glycerol and stir evenly to obtain the sodium alginate membrane stock solution.
7. An application of UiO-66-NH2@Lac@SA membrane, characterized in that: The UiO-66-NH2@Lac@SA membrane is used for wastewater treatment.
8. The use according to claim 7, characterized in that: The UiO-66-NH2@Lac@SA membrane is used to degrade dyes.
Citation Information
Patent Citations
Lipoic acid modified gold ion adsorbent, preparation method and applications thereof
CN110105328A
Co-immobilized enzyme and preparation method and application thereof
CN110628756A
UiO-66-NH2-coated ANFs aerogel as well as preparation method and application thereof
CN116656135A
Constructed wetland system enhanced by immobilized laccase
US20230048966A1
